2016
DOI: 10.1186/s12916-016-0682-7
|View full text |Cite
|
Sign up to set email alerts
|

Predictive validity of the UKCAT for medical school undergraduate performance: a national prospective cohort study

Abstract: BackgroundThe UK Clinical Aptitude Test (UKCAT) has been shown to have a modest but statistically significant ability to predict aspects of academic performance throughout medical school. Previously, this ability has been shown to be incremental to conventional measures of educational performance for the first year of medical school. This study evaluates whether this predictive ability extends throughout the whole of undergraduate medical study and explores the potential impact of using the test as a selection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 28 publications
5
48
1
Order By: Relevance
“…6 Moreover, the predictor-outcome coefficients we observed in the present review are frequently similar in magnitude, and sometimes larger, compared to those cited for cognitive assessments used to evaluate problem-solving ability in medical school applicants. [59][60][61][62] There Over half (n = 17) of the studies 17,27,[30][31][32]37,38,[40][41][42][43]45,46,48,51,52,55 identified attempted to estimate the incremental validity of the SJT being evaluated, above and beyond other selection assessments, such as tests of cognitive ability, academic performance and clinical knowledge. Of those that did, only two 31,45 did not report any evidence of incremental validity.…”
Section: Ta B L E 2 Results From the Univariable And Multivariable Mementioning
confidence: 99%
See 1 more Smart Citation
“…6 Moreover, the predictor-outcome coefficients we observed in the present review are frequently similar in magnitude, and sometimes larger, compared to those cited for cognitive assessments used to evaluate problem-solving ability in medical school applicants. [59][60][61][62] There Over half (n = 17) of the studies 17,27,[30][31][32]37,38,[40][41][42][43]45,46,48,51,52,55 identified attempted to estimate the incremental validity of the SJT being evaluated, above and beyond other selection assessments, such as tests of cognitive ability, academic performance and clinical knowledge. Of those that did, only two 31,45 did not report any evidence of incremental validity.…”
Section: Ta B L E 2 Results From the Univariable And Multivariable Mementioning
confidence: 99%
“…In this regard, numerical simulation methods, such as those previously applied to medical selection situations, may be useful. 5,60 As the widespread use of SJTs in under- More generally, it should be highlighted that all the included studies were from high-income countries. Previous research has found that SJT methodology is typically transportable for use in recruitment settings in other countries.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…A levels are Graded A* to F, with A* being the highest grade and typically medical schools require three A levels with A* or A grades. Studies have reported academic attainment and UCAT scores to be significant predictors of medical school outcome [13,14]. Mwandigha et al, who found UCAT scores added some predictive value in addition to secondary school achievement for undergraduate academic performance, supports this [15].…”
Section: Introductionmentioning
confidence: 87%
“…Undergraduate Medical and Health Sciences Aptitude Test; UMAT) versus hybrids of the two types (e.g., the Medical College Admissions Test MCAT 2015). Performance on aptitude tests has been compared to mainly midpoint or endpoint training outcome measures, such as exam performance early in the curriculum (McManus, Dewberry, Nicholson, & Dowell, 2013) and at the end of medical school (Tiffin et al, 2016). There is equivocal evidence that aptitude tests may or may not favour certain types of candidates, which may have implications for fairness and widening access to medicine (Tiffin, Dowell, & McLachlan, 2012;Lievens, Patterson, Corstjens, Martin, & Nicholson, 2016;Kumar, Roberts, Bartle, & Eley, 2018).…”
mentioning
confidence: 99%